Multidrug-resistant tuberculosis: case reports study in a central state of Brazil - Araújo-Filho,João Alves de (2008)
Multidrug-resistant tuberculosis (MDR-TB) is an emerging and worrisome health problem that threatens tuberculosis (TB) control worldwide. The clinical management of MDR-TB is a complex issue associated with the use of multiple drugs for a long period, usually accompanied by side effects and high costs. The objective of this work was to relate cases of MDR-TB occurring in Goiás, a central state of Brazil. We related five cases of MDR-TB, three women and two men. All were pulmonary cases. Three were in their second treatment and two in their first treatment. Surgical pulmonary resection was performed in one case. One death occurred. Lack of adherence, gastric intolerance to anti-TB drugs and poor clinical management were the main aspects related to the emergent resistance. A revision of the main clinical aspects of this disease was performed.